Heat exchanger design handbook - Kuppan, T., 1957- (Boca Raton, FL : CRC Press, 2013)
'This comprehensive reference covers all the important aspects of heat exchangers (HEs): design and modes of operation and practical, large-scale applications in process, power, petroleum, transport, air conditioning, refrigeration, cryogenics, heat recovery, energy, and other industries. It includes over 400 drawings, diagrams, tables, and equations, making it a great resource for mechanical, chemical, and petrochemical engineers; process equipment and pressure vessel designers; and upper-level undergraduate and graduate students. This second edition includes updated material throughout; coverage of the latest advances in HE design techniques; expanded and updated coverage of materials selection; and a look at the newest fabrication techniques'--
Heat exchangers: introduction, classification, and selection -- Heat exchanger thermohydraulic fundamentals -- Heat exchanger thermal design -- Compact heat exchangers -- Shell and tube heat exchanger design -- Regenerators -- Plate heat exchangers and spiral plate heat exchangers -- Heat transfer augmentation -- Fouling -- Flow-induced vibration of shell and tube heat exchangers -- Mechanical design of shell and tube heat exchangers -- Corrosion -- Material selection and fabrication -- Quality control and quality assurance, inspection, and nondestructive testing -- Heat exchanger fabrication -- Heat exchanger installation, operation, and maintenance.
Includes bibliographical references and index.
Keywords: Heat exchangers -- Design and construction -- Handbooks, manuals, etc